1992
DOI: 10.1021/bp00013a009
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometric Evaluation of β‐Lactoglobulin Adsorption onto Low‐and High‐Energy Materials

Abstract: Ellipsometry was used to study solid-surface energetic and temperature effects on the apparent equilibrium adsorptive behavior exhibited by ,&lactoglobulin. Adsorption isotherms were constructed for ,&lactoglobulin on seven different silicon surfaces chemically modified to exhibit varying hydrophobicities: plateau values of adsorbed mass were observed to increase with increasing degree of solid-surface silanization with dichlorodimethylsilane. &Lactoglobulin isotherms at 2,27, and 52 "C were constructed on uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…They concluded that the denaturation of β-lactoglobulin was irreversible whereas denaturation of α-lactalbumin was highly reversible. Almalah et al (36) confirmed that high temperature increases the adsorption of β-lactoglobulin on hydrophilic and hydrophobic silicon. Elofsson et al (14) found adsorption during heat treatment was related to thermal unfolding and aggregation of β-lactoglobulin.…”
Section: Discussionmentioning
confidence: 96%
“…They concluded that the denaturation of β-lactoglobulin was irreversible whereas denaturation of α-lactalbumin was highly reversible. Almalah et al (36) confirmed that high temperature increases the adsorption of β-lactoglobulin on hydrophilic and hydrophobic silicon. Elofsson et al (14) found adsorption during heat treatment was related to thermal unfolding and aggregation of β-lactoglobulin.…”
Section: Discussionmentioning
confidence: 96%
“…There we set up a system for in situ detection of protein adsorption by ellipsometry [1] and began quantifying surface and protein properties affecting the rate and extent of protein adsorption from single-protein solutions [2][3][4][5][6][7]. We worked mainly with the milk proteins ˛-lactalbumin, ˇ-lactoglobulin, BSA, and ˇ-casein.…”
Section: The Beginningmentioning
confidence: 99%
“…Malmsten (12) and Lassen (13) describe competitive adsorption from binary Luggin reference electrode; (2) solution inlet; (3) platinum counter elecprotein solutions. Al-Malah et al (14) measure adsorption trode; (4) working electrode. of b-lactoglobulin onto a variety of surfaces, finding the greatest adsorption onto glass and the least onto stainless steel, the latter showing an adsorption of 4 mg/m 2 .…”
Section: Introductionmentioning
confidence: 99%